Digital Marketing Synergy and Green Innovation: A New Paradigm of Marketing Management in Sustainability-Based Economic Development - Lukitasari, Lenni; Ni Luh Gde Sari Dewi Astuti; Sofyan, Hady; Hartoto (International Journal of Economics (IJEC), 2025)
Greenhope is a green technology-based company in Indonesia that focuses on developing environmentally friendly products, such as biodegradable plastics, in response to the global issues of sustainability and environmental pollution. In the context of modern marketing, companies like Greenhope face the challenge of innovating green and utilizing digital marketing strategies to shape positive consumer perceptions of sustainability values. This study aims to analyze the effect of synergy between digital marketing and green innovation on consumer perceptions of green brands as well as their impact on marketing performance and contribution to sustainability-based economic development. The research method used was quantitative explanatory with data collection techniques through questionnaires distributed online to consumers who know or use Greenhope products. Data analysis was performed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results show that both digital marketing and green innovation have a significant and positive influence on consumers’ perceptions of green brands. Furthermore, perceptions of green brands have been shown to positively contribute to marketing performance and consumer perceptions of a company's sustainability commitment. In practice, these findings demonstrate the importance of integrating digital marketing strategies and green innovation to build a company's competitive position in the era of a sustainable economy. Companies are advised to consistently communicate green values ​​ through digital platforms to strengthen consumer loyalty and awareness of environmental issues